2012
DOI: 10.15288/jsad.2012.73.885
|View full text |Cite
|
Sign up to set email alerts
|

Are Social Network Correlates of Heavy Drinking Similar Among Black Homeless Youth and White Homeless Youth?

Abstract: ABSTRACT. Objective: Understanding factors associated with heavy drinking among homeless youth is important for prevention efforts. Social networks are associated with drinking among homeless youth, and studies have called for attention to racial differences in networks that may affect drinking behavior. This study investigates differences in network characteristics by the racial background of homeless youth, and associations of network characteristics with heavy drinking. (Heavy drinking was defi ned as havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…As Table , item 4 indicates, exposure to mental and physical health risks as well as prevalence of high‐risk behaviors differ between non‐white and white homeless youth. In a study of Los Angeles homeless youths ages 13–24, Wenzel et al () found that black youth were more connected to networks that included people who regularly attended school, whereas white youth were more connected to networks of people who drank to intoxication and were homeless. For white youth but not black youth, a significant association was found between heavy drinking behavior and connection to peers who drank heavily.…”
Section: Race and Youth Homelessnessmentioning
confidence: 99%
“…As Table , item 4 indicates, exposure to mental and physical health risks as well as prevalence of high‐risk behaviors differ between non‐white and white homeless youth. In a study of Los Angeles homeless youths ages 13–24, Wenzel et al () found that black youth were more connected to networks that included people who regularly attended school, whereas white youth were more connected to networks of people who drank to intoxication and were homeless. For white youth but not black youth, a significant association was found between heavy drinking behavior and connection to peers who drank heavily.…”
Section: Race and Youth Homelessnessmentioning
confidence: 99%
“…Os estudos encontrados na revisão apontam para metodologias comparativas (Gattis, 2013;Wenzel et al, 2012) e para a inter-relação de variáveis (Bobashev et al, 2009;Shoptaw et al, 2009), sendo analisadas as categorias: sexualidade, raça, gênero, pobreza e estigma. Além disso, partem de uma leitura a partir do conceito de "risco".…”
Section: Os Trabalhos Estadunidenses 3 E Do Norte: O Conceito De "Risunclassified
“…Further, opportunities exist to develop cross-system and crosssector collaboration to improve responses to homelessness and avoid punitive actions such as criminalizing homelessness (Aykanian & Lee, 2016). Finally, there is increasing attention to the role that social networks play in homelessness and the risk behaviors engaged in by people experiencing homelessness, suggesting that existing homeless services could do more to address social support (de la Haye, Green, Kennedy, Wenzel, & Tucker, 2012;Green, Tucker, Kennedy, & Wenzel, 2013;Song & Wenzel, 2014;Wenzel, Holloway, Golinelli, Bowman, & Tucker, 2011;Wenzel, Hsu, Zhou, & Tucker, 2012).…”
Section: Workforce Development and Service Needs: Implications For Social Workmentioning
confidence: 99%